FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMEN MEMILIH RESTO SALESA TRENGGALEK - Belviana, Lifsa; Samari, Samari; Purnomo, Hery (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
Consumer buying interest assessment is required by employers to know the development of consumers to the advantages and disadvantages that exist to the selection of the intended product. In order for the business to be achieved consumer buying interest, the entrepreneur must look at the factors of product quality, place, and service that affect the consumer's buying interest in this culinary business. This research uses quantitative approach with Survey method. sampling is used with nonprobability sampling and sampling techniques by Accidental sampling, research samples as many as 40 respondents. instruments in the study are questionnaires (questionnaires), data analysis using linear regression. The results of the study found that the quality of products, places, and services partially influenced the consumer buying interest Resto Salesa Trenggalek, and the quality of products, places, and services simultaneously significantly influenced the buying interest of consumers Resto Salesa Trenggalek.